The Effect of Current Ratio, Debt to Equity Ratio and Return in The Consumer Goods Industry Sector Listed in Indonesia Stock Exchange 2012-2017 - Amelia, Yusi; Asmara, Rina Y (International Humanities and Applied Science Journal, 2019)
This study aims to analyze the effect of current ratio (CR), debt to equity ratio (DER), and return on equity ratio (ROE) on dividend payout ratio (DPR) in the consumer goods industry sector listed in Indonesia Stock Exchange period of 2012-2017. The sample selection in this study using purposive sampling method and got 13 companies that match the criteria. From result of research got value of adjusted R-Square equal to 62.64%. It indicated that return on equity has a significant negative effect on dividend payout ratio with regression coefficient equal to -1.070932. However, the result of current ratio has insignificant negative effect on the dividend payout ratio with regression coefficient of -2.462612 and debt to equity ratio has insignificant positive effect on the dividend payout ratio with regression coefficient of 0.012540.